Overexpression of PvPin1, a Bamboo Homolog of PIN1-Type Parvulin 1, Delays Flowering Time in Transgenic Arabidopsis and Rice - Zheng, Zhigang; Yang, Xiaoming; Fu, Yaping; Zhu, Longfei; Wei, Hantian; Lin, Xinchun (Frontiers in Plant Science, 2017)
Because of the long and unpredictable flowering period in bamboo, the molecular mechanism of bamboo flowering is unclear. Recent study showed that Arabidopsis PIN1-type parvulin 1 (Pin1At) is an important floral activator and regulates floral transition by facilitating the cis/trans isomerization of the phosphorylated Ser/Thr-Pro motifs in SUPPRESSOR OF OVEREXPRESSION OF CO 1 (SOC1) and AGAMOUS-LIKE 24 (AGL24). Whether bamboo has a Pin1 homolog and whether it works in bamboo flowering is still unknown. In this study, we cloned PvPin1, a homolog of Pin1At, from Phyllostachys violascens (Bambusoideae). Bioinformatics analysis showed that PvPin1 is closely related to Pin1-like proteins in monocots. PvPin1 was widely expressed in all tested bamboo tissues, with the highest expression in young leaf and lowest in floral bud. Moreover, PvPin1 expression was high in leaves before bamboo flowering then declined during flower development. Overexpression of PvPin1 significantly delayed flowering time by downregulating SOC1 and AGL24 expression in Arabidopsis under greenhouse conditions and conferred a significantly late flowering phenotype by upregulating OsMADS56 in rice under field conditions. PvPin1 showed subcellular localization in both the nucleus and cytolemma. The 1500-bp sequence of the PvPin1 promoter was cloned, and cis-acting element prediction showed that ABRE and TGACG-motif elements, which responded to abscisic acid (ABA) and methyl jasmonate (MeJA), respectively, were characteristic of P. violascens in comparison with Arabidopsis. On promoter activity analysis, exogenous ABA and MeJA could significantly inhibit PvPin1 expression. These findings suggested that PvPin1 may be a repressor in flowering, and its delay of flowering time could be regulated by ABA and MeJA in bamboo.